Battery and preparation method thereof
By using specific types of sodium salts and solvents in the electrolyte of sodium-ion batteries, and controlling the mass proportion of the solvent, the problem of low energy density caused by the high mass proportion of the electrolyte is solved, and the battery energy density and cycle life are improved. promote.
Patent Information
- Application Number
- CN202411508343.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
AI Technical Summary
The mass proportion of electrolyte in sodium ion batteries is high, resulting in a low energy density. How to reduce the mass proportion of electrolyte is an urgent problem to be solved.
By using the first type of sodium and solvents in the electrolyte of the battery, specifically, carbonate and linear carbonate, linear carbonate, linear carbonate, and linear ether are used as solvents, and the quality of the first type of solvent is controlled Battery with low electrolyte density between 8 % and 15 % ratio.
The quality proportion of electrolytes is reduced, the energy density and cycle life of the battery is increased, and the infiltration of the electrolyte to the polar sheet is improved, and the injection coefficient of the electrolyte is reduced.
Smart Images

Figure BDA0005104688210000141 
Figure BDA0005104688210000151 
Figure BDA0005104688210000152
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery and a method for preparing the battery. Background Art
[0002] Sodium-ion batteries have attracted extensive attention in the industry in the development of new generation energy storage systems due to their abundant sodium reserves, low cost and good cycle stability. However, due to the high mass proportion of electrolyte in sodium-ion batteries, the energy density of sodium-ion batteries is low. How to reduce the mass proportion of electrolyte in sodium-ion batteries is an urgent problem to be solved. Summary of the invention
[0003] Purpose of the invention: The present application provides a battery and a method for preparing the same. The battery has a low electrolyte density, which is beneficial to reducing the mass proportion of the electrolyte in the sodium ion battery and enabling the battery to have a higher energy density and cycle life.
[0004] The first aspect of the present application provides a battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises a first injection electrolyte and a second injection electrolyte, wherein the first injection electrolyte and the second injection electrolyte both comprise a first type of sodium salt and a solvent; the solvent comprises a first type of solvent and a second type of solvent, wherein the first type of solvent is selected from at least one of propylene carbonate and ethylene carbonate, and the second type of solvent is selected from at least one of linear carbonates, linear carboxylates and linear ethers, and the mass proportion of the first type of solvent, based on the total mass of the solvent, is w0, satisfying: 8%≤w0≤15wt%.
[0005] In some embodiments, the electrolyte solution further includes a first type of additive and a second type of additive, the first type of additive is selected from at least one of a second type of sodium salt and a second type of lithium salt, and the second type of additive is selected from esters;
[0006] The first type of sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, and sodium tetraphenylborate;
[0007] The linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate;
[0008] The linear carboxylic acid ester is selected from at least one of ethyl acetate, methyl acetate and methyl propionate;
[0009] The linear ether is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether;
[0010] The second type of sodium salt is selected from at least one of sodium difluorophosphate, sodium difluorooxalatoborate, sodium tetrafluorooxalatophosphate, sodium trifluoromethanesulfonate, and sodium tetrafluoroborate;
[0011] The lithium salt is selected from at least one of lithium difluorooxalatoborate and lithium tetrafluorooxalatophosphate;
[0012] The ester is selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and tris(trimethylsilyl)phosphate.
[0013] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the first type of additive is w1, and the mass proportion of the second type of additive is w2, which satisfies: 10% <w1 / (w1+w2)<40%;
[0014] Based on the total mass of the electrolyte injection, the mass proportion of the first type of additive is w1, which satisfies: 0.5wt%≤w1≤1.0wt%;
[0015] Based on the total mass of the one injection of electrolyte, the mass proportion of the second type of additive is w2, satisfying: 2.5wt%≤w2≤4.0wt%;
[0016] Based on the total mass of the one injection of electrolyte, the mass proportion of the first type of sodium salt is w3, satisfying: 10wt%≤w3≤15wt%;
[0017] Based on the total mass of the electrolyte injection, the mass proportion of the solvent is w4, satisfying: 80wt≤w4≤87wt%.
[0018] In some embodiments, the second injection electrolyte further includes a third type of additive, and the third type of additive is selected from vinylene carbonate;
[0019] The first type of sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, and sodium tetraphenylborate;
[0020] The linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate;
[0021] The linear carboxylic acid ester is selected from at least one of ethyl acetate, methyl acetate and methyl propionate;
[0022] The linear ether is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether;
[0023] In some embodiments, based on the total mass of the two electrolyte injections, the mass proportion of the third type of additive is w5, satisfying: 5wt%≤w5≤15wt%;
[0024] Based on the total mass of the two electrolytes, the mass proportion of the first type of sodium salt is w6, satisfying: 10wt%≤w6≤15wt%;
[0025] Based on the total mass of the two-injection electrolyte, the mass proportion of the solvent is w7, satisfying: 70wt% ≤ w7 ≤ 85wt%.
[0026] In some embodiments, the mass ratio of the first-injection electrolyte to the second-injection electrolyte is 3 - 9:1.
[0027] In some embodiments, the battery satisfies the following expression: 110wh / kg < QU / m < 120wh / kg, and 15% < m1 / m < 20%;
[0028] where Q represents the capacity of the battery, in wh; U represents the average discharge voltage of the battery when the discharge voltage is 1.5V - 3.8V, in V; m1 represents the mass of the electrolyte, in kg, and m represents the mass of the battery, in kg. The battery satisfies the following expression: 110wh / kg < QU / m < 120wh / kg, and 15% < m1 / m < 20%.
[0029] In some embodiments, the average density of the electrolyte is ρ, satisfying: 1.10 < ρ < 1.15g / ml.
[0030] In some embodiments, the tap density of the positive electrode is 2.1 - 2.3g / cm 3 .
[0031] In some embodiments, the areal density of the positive electrode is 20 - 22mg cm -2 .
[0032] In some embodiments, the tap density of the negative electrode is 0.95 - 0.98g / cm 3 .
[0033] In some embodiments, the areal density of the negative electrode is 7.1 - 7.3mg cm -2 .
[0034] In some embodiments, the positive electrode includes a positive current collector and a positive electrode material located on at least one side of the positive current collector. The positive electrode material includes a positive electrode active material, and the positive electrode active material is selected from at least one of sodium iron pyrophosphate phosphate and sodium iron phosphate. Based on the total mass of the positive electrode material, the mass proportion of the positive electrode active material is 95 - 96.5%.
[0035] In some embodiments, the negative electrode includes a negative current collector and a negative electrode material located on at least one side of the negative current collector. The negative electrode material includes a negative electrode active material, and the negative electrode active material is selected from hard carbon. Based on the total mass of the negative electrode material, the mass proportion of the negative electrode active material is 95 - 96.5%.
[0036] The third aspect of the present application provides a method for preparing a battery, comprising:
[0037] Provide positive electrode sheets, negative electrode sheets and separators;
[0038] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a winding core;
[0039] After the roll core is packaged, a roll core to be injected with liquid is obtained;
[0040] Injecting a shot of electrolyte into the core to be injected to obtain a shot of battery cell;
[0041] After precharging and aging the one-shot battery cell, injecting a second shot of electrolyte into the one-shot battery cell to obtain a second shot of electrolyte;
[0042] After the two battery cells are combined, a battery is obtained.
[0043] In some embodiments, the injection coefficient of the electrolyte injection is 2.8 to 3 g / Ah.
[0044] In some embodiments, the injection coefficient of the two injections of electrolyte is 0.6 to 1.0 g / Ah.
[0045] The present application provides a battery, including: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte includes a first-injection electrolyte and a second-injection electrolyte, wherein the first-injection electrolyte and the second-injection electrolyte both include a first-type sodium salt and a solvent; wherein the solvent includes a first-type solvent and a second-type solvent, wherein the first-type solvent is selected from propylene carbonate, and the second-type solvent is selected from at least one of carboxylic acid esters and ethers, and the mass proportion of the first-type solvent is w0 based on the total mass of the solvent, satisfying: 8%≤w0≤15wt%. Among them, the first-type solvent has high viscosity and high density, and the second-type solvent has low density and low viscosity. The present application adopts the first-type solvent and the second-type solvent as solvents of the electrolyte, and controls the mass proportion w0 of the first-type solvent in the solvent to satisfy 8wt%≤w0≤15wt%, and the prepared electrolyte has low density, which can improve the wettability of the electrolyte to the electrode sheet, reduce the injection coefficient of the electrolyte, and also improve the energy density of the battery. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0047] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0048] The first aspect of the present application provides a battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises a first injection electrolyte and a second injection electrolyte, wherein the first injection electrolyte and the second injection electrolyte both comprise a first type of sodium salt and a solvent; the solvent comprises a first type of solvent and a second type of solvent, wherein the first type of solvent is selected from at least one of propylene carbonate and ethylene carbonate, and the second type of solvent is selected from at least one of linear carbonates, linear carboxylates and linear ethers, and the mass proportion of the first type of solvent, based on the total mass of the solvent, is w0, satisfying: 8%≤w0≤15wt%.
[0049] It can be understood that the first type of solvent has high viscosity and high density, while the second type of solvent has low density and low viscosity. The present application adopts the first type of solvent and the second type of solvent as the solvent of the electrolyte, and controls the mass proportion w0 of the first type of solvent in the solvent to satisfy 8wt%≤w0≤15wt%. The prepared electrolyte has low density, which can improve the wettability of the electrolyte to the electrode, reduce the injection coefficient of the electrolyte, and at the same time improve the energy density of the battery.
[0050] In some embodiments, a shot of electrolyte further includes a first type of additive and a second type of additive, the first type of additive is selected from at least one of the second type of sodium salt and lithium salt, and the second type of additive is selected from esters.
[0051] It can be understood that since the second type of solvent has low density, low viscosity and low oxidation resistance, by adding the first type of additives and the second type of additives to the electrolyte, a corresponding protective film can be formed on the surface of the positive and negative electrodes, which can inhibit further decomposition of the electrolyte and thus improve the cycle life of the electrolyte.
[0052] In some embodiments, the first type of sodium salt in an electrolyte is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, sodium tetraphenylborate;
[0053] It can be understood that the first type of sodium salt, as the main salt of the electrolyte, mainly provides the functions of ion conduction and charge balance.
[0054] In some embodiments, the linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.
[0055] In some embodiments, the linear carboxylic acid ester is selected from at least one of ethyl acetate (EA), methyl acetate (MA), and methyl propionate (MP).
[0056] It can be understood that linear carboxylic acid esters have low density and low viscosity, which can improve the conductivity and wettability of the electrolyte.
[0057] In some embodiments, the linear ethers are selected from at least one of ethylene glycol dimethyl ether (DME) and diethylene glycol dimethyl ether (DGME).
[0058] It can be understood that small molecule linear ethers have low density and low viscosity, which can improve the conductivity and wettability of the electrolyte.
[0059] In some embodiments, the second type of sodium salt is selected from at least one of sodium difluorophosphate, sodium difluorooxalate borate, lithium tetrafluorooxalate phosphate, sodium trifluoromethanesulfonate, and sodium tetrafluoroborate;
[0060] It can be understood that when the first type of additive selects the second type of sodium salt, the thermal stability of the film formation is better, which can improve the calendar life of the battery cell.
[0061] In some embodiments, the lithium salt is selected from at least one of lithium difluorooxalate borate (LiDFOB) and lithium tetrafluorooxalate phosphate (LiDFOP).
[0062] It can be understood that when the first type of additive selects the lithium salt, it can achieve a similar effect to that of the second type of sodium salt to improve the calendar life of the battery cell.
[0063] In some embodiments, the esters are selected from at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), divinyl sulfate (DTD), and tris(trimethylsilyl) phosphate (TMSP).
[0064] It can be understood that when the second type of additive selects esters, corresponding protective films can be formed on the positive and negative electrode surfaces, which can inhibit the further decomposition of the electrolyte, thereby improving the cycle life of the electrolyte.
[0065] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the first type of additive is w1, and the mass fraction of the second type of additive is w2, satisfying: 10% < w1 / (w1 + w2) < 40%. Specifically, the value of w1 / (w1 + w2) can be any one value or a range composed of any two values among 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%.
[0066] It can be understood that the first type of additive is at least one of the second type of sodium salts and lithium salts, and the second type of additive is an ester. Based on the total mass of the electrolyte, the mass fraction w1 of the first type of additive and the mass fraction w2 of the second type of additive satisfy 10% < w1 / (w1 + w2) < 40%. On the premise of ensuring the cycle life of the electrolyte, the stability of the surface SEI film is further optimized, and the calendar life of the battery cell is improved.
[0067] In some embodiments, based on the total mass of a single injection of electrolyte, the mass fraction of the first type of additive is w1, satisfying: 0.5 wt% ≤ w1 ≤ 1.0 wt%.
[0068] In some embodiments, based on the total mass of a single injection of electrolyte, the mass fraction of the second type of additive is w2, satisfying: 2.5 wt% ≤ w2 ≤ 4.0 wt%.
[0069] In some embodiments, based on the total mass of a single injection of electrolyte, the mass fraction of the first type of sodium salt is w3, satisfying: 10 wt% ≤ w3 ≤ 15 wt%. Specifically, the value of w3 can be any one value or the range composed of any two values among 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%.
[0070] In some embodiments, based on the total mass of a single injection of electrolyte, the mass fraction of the solvent is w4, satisfying: 80 wt% ≤ w4 ≤ 87 wt%.
[0071] In some embodiments, the second injection of electrolyte further includes a third type of additive, and the third type of additive is selected from vinylene carbonate (VC).
[0072] It can be understood that the third type of additive is selected from vinylene carbonate, which can form a corresponding protective film on the positive and negative electrodes, inhibit the further decomposition of the electrolyte, and thus improve the cycle life of the electrolyte.
[0073] In some embodiments, the first type of sodium salt in the second injection of electrolyte is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium tetraphenylborate;
[0074] In some embodiments, the linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.
[0075] In some embodiments, the linear carboxylic acid ester is selected from at least one of ethyl acetate (EA), methyl acetate (MA), and methyl propionate (MP).
[0076] In some embodiments, the linear ether is selected from at least one of ethylene glycol dimethyl ether (DME) and diethylene glycol dimethyl ether (DGME).
[0077] In some embodiments, based on the total mass of the two injections of electrolyte, the mass proportion of the third type of additive is w5, satisfying: 5wt%≤w5≤15wt%.
[0078] It can be understood that the third type of additive is selected from vinylene carbonate (VC). By controlling the mass proportion w5 of the third type of additive in the electrolyte to satisfy 5wt%≤w5≤15wt%, the high temperature performance of the electrolyte can be improved while ensuring the normal temperature cycle life of the electrolyte.
[0079] In some embodiments, based on the total mass of the two electrolyte injections, the mass proportion of the first type of sodium salt is w6, satisfying: 10wt%≤w6≤15wt%. Specifically, the value of w6 can be any one of 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, or a range consisting of any two values.
[0080] In some embodiments, based on the total mass of the two electrolyte injections, the mass proportion of the solvent is w7, satisfying: 70wt%≤w7≤85wt%.
[0081] It can be understood that the electrolyte provided in the present application has a low density. By using the electrolyte provided in the present application to prepare a battery, the wettability of the electrolyte to the electrode can be improved, the injection coefficient of the electrolyte can be reduced, and the energy density of the battery can also be improved.
[0082] In some embodiments, the mass ratio of the first electrolyte injection to the second electrolyte injection is 3-9: 1. It is understood that when the mass ratio of the first electrolyte injection to the second electrolyte injection is between 9: 1 (90%: 10%) and 3: 1 (75%: 25%), it is possible to ensure that the battery cell has both good wettability and cycle performance.
[0083] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode material located on at least one side of the positive electrode current collector, the positive electrode material includes a positive electrode active material, the positive electrode active material is selected from at least one of sodium ferric phosphate pyrophosphate and sodium ferric phosphate, and the mass proportion of the positive electrode active material is 95 to 96.5% based on the total mass of the positive electrode material. Specifically, the mass proportion of the positive electrode active material can be any one of 95%, 95.5%, 96%, and 96.5%, or a range consisting of any two values, based on the total mass of the positive electrode material.
[0084] It can be understood that by controlling the mass proportion of the positive electrode active material in the positive electrode material to 95-96.5%, the gram capacity and compaction density of the positive electrode material can be increased, thereby increasing the energy density of the battery.
[0085] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode material located on at least one side of the negative electrode current collector. The negative electrode material includes a negative electrode active material, and the negative electrode active material is selected from hard carbon. Based on the total mass of the negative electrode material, the mass percentage of the negative electrode active material is 95-96.5%. Specifically, based on the total mass of the negative electrode material, the mass percentage of the negative electrode active material can be any value among 95%, 95.5%, 96%, 96.5% or a range composed of any two of these values.
[0086] It can be understood that by controlling the mass percentage of the negative electrode active material in the negative electrode material to be 95-96.5%, the specific capacity and tap density of the negative electrode material can be improved, thereby improving the energy density of the battery.
[0087] In some embodiments, Q represents the capacity of the battery, with the unit of wh; U represents the average discharge voltage of the battery when the discharge voltage is 1.5V-3.8V, with the unit of V; m1 represents the mass of the electrolyte, with the unit of kg, and m represents the mass of the battery, with the unit of kg. The battery satisfies the following expression: 110wh / kg < QU / m < 120wh / kg, and 15% < m1 / m < 20%.
[0088] It can be understood that by controlling the mass m1 of the electrolyte in the battery to satisfy 15% < m1 / m < 20%, the energy density of the battery can reach more than 110wh / kg.
[0089] In some embodiments, the density of the electrolyte is ρ, satisfying: 1.10g / ml < ρ < 1.15g / ml. Specifically, the density ρ of the electrolyte can be any value among 1.12, 1.13, 1.14 or a range composed of any two of these values.
[0090] It can be understood that by controlling the density ρ of the electrolyte to satisfy 1.10g / ml < ρ < 1.15g / ml, the usage amount of the electrolyte in the battery is reduced by more than 25% compared with the usage amount of the traditional carbonate electrolyte, thereby improving the energy density of the battery.
[0091] In some embodiments, the tap density of the positive electrode is 2.1-2.3g / cm 3 . Specifically, the tap density of the positive electrode can be 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 or any value among these or a range composed of any two of these values.
[0092] It can be understood that by controlling the tap density of the positive electrode to be 2.1-2.3g / cm 3 , the energy density of the battery can be improved.
[0093] In some embodiments, the surface density of the positive electrode is 20 to 22 mg cm -2 Specifically, the surface density of the positive electrode can be 20 mg cm -2 , 21mg cm -2 , 22mg cm -2 Any value or a range of any two values in .
[0094] It can be understood that by controlling the surface density of the positive electrode to 20-22 mg cm -2 , which can improve the energy density of the battery.
[0095] In some embodiments, the compaction density of the negative electrode is 0.95 to 0.98 g / cm 3 Specifically, the compaction density of the negative electrode can be 0.95 g / cm 3 , 0.96g / cm 3 , 0.97g / cm 3 、0.98g / cm 3 Any value or a range of any two values in .
[0096] It can be understood that by controlling the compaction density of the negative electrode to 0.95-0.98 g / cm 3 , which can improve the energy density of the battery.
[0097] In some embodiments, the surface density of the negative electrode is 7.1 to 7.3 mg cm -2 Specifically, the surface density of the negative electrode can be 7.1 mg cm -2 、7.2mg cm -2 、7.3mg cm -2 Any value or a range of any two values in .
[0098] It can be understood that by controlling the surface density of the negative electrode to 7.1-7.3 mg cm -2 , which can improve the energy density of the battery.
[0099] The third aspect of the present application provides a method for preparing a battery, comprising:
[0100] Step S1: providing a positive electrode sheet, a negative electrode sheet and a separator;
[0101] Step S2: stacking the positive electrode sheet, the negative electrode sheet and the separator to obtain a winding core;
[0102] Step S3: After the core is packaged, a core to be injected is obtained;
[0103] Step S4: injecting a shot of electrolyte into the core to be injected to obtain a shot of battery cell;
[0104] Step S5: After precharging and aging the first battery cell, injecting the second electrolyte into the first battery cell to obtain the second battery cell;
[0105] Step S6: After the two battery cells are formed, a battery is obtained.
[0106] In some embodiments, the present application also provides a method for preparing a positive electrode sheet, comprising:
[0107] Mixing a positive electrode active material, a first conductive agent, a first binder and N-methylpyrrolidone to obtain a positive electrode slurry;
[0108] The positive electrode slurry is coated on the positive electrode current collector, dried at 60° C., and then roll-pressed and die-cut to obtain a positive electrode sheet.
[0109] In some embodiments, the first conductive agent is selected from at least one of conductive carbon black and carbon nanotubes.
[0110] In some embodiments, the first binder is selected from at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0111] In some embodiments, the present application also provides a method for preparing a negative electrode sheet, comprising:
[0112] Mixing the negative electrode active material, the second conductive agent, the wetting agent, the second binder and deionized water to obtain a negative electrode slurry;
[0113] The negative electrode slurry is coated on the negative electrode current collector, dried at 80° C., and then roll-pressed and die-cut to obtain a negative electrode sheet.
[0114] In some embodiments, the second conductive agent is selected from at least one of conductive carbon black and carbon nanotubes.
[0115] In some embodiments, the second binder is selected from at least one of styrene-butadiene rubber (SBR) and sodium polyacrylate (PAANa).
[0116] In some embodiments, the wetting agent is selected from at least one of sodium carboxymethyl cellulose (CMC-Na) and sodium polyacrylate (PAANa).
[0117] In some embodiments, the present application also provides a method for preparing an electrolyte, comprising:
[0118] Mixing the first sodium salt, the first solvent, the second solvent, the first additive and the second additive to obtain an electrolyte;
[0119] The first sodium salt, the first solvent, the second solvent and the third additive are mixed to obtain two injections of electrolyte.
[0120] In some embodiments, the injection coefficient of one injection of electrolyte is 2.8-3 g / Ah. Specifically, the injection coefficient of one injection of electrolyte can be any one of 2.8 g / Ah, 2.9 g / Ah, 3 g / Ah, or a range consisting of any two values.
[0121] It can be understood that by controlling the injection coefficient of an electrolyte injection to 2.8 to 3 g / Ah, the amount of electrolyte used in the battery can be reduced, thereby increasing the energy density of the battery.
[0122] In some embodiments, the electrolyte injection coefficient of the two-shot battery cell is 0.6 to 1.0 g / Ah. Specifically, the electrolyte injection coefficient of the two-shot battery cell can be any one of 0.6 g / Ah, 0.65 g / Ah, 0.7 g / Ah, 0.75 g / Ah, 0.8 g / Ah, 0.85 g / Ah, 0.9 g / Ah, 0.95 g / Ah, and 1.0 g / Ah, or a range consisting of any two values.
[0123] It can be understood that by controlling the injection coefficient of the second injection of electrolyte to 0.6-1.0 g / Ah, the amount of electrolyte used in the battery can be reduced, thereby improving the energy density of the battery.
[0124] The following will describe in conjunction with specific embodiments.
[0125] Example 1
[0126] Preparation of positive electrode sheet: The positive electrode active material sodium ferric pyrophosphate, the first conductive agent conductive carbon black, and the first binder polyvinylidene fluoride are mixed in a mass ratio of 95:2.5:2.5. During the mixing process, N-methylpyrrolidone is used to prepare the mixture into a positive electrode slurry with a solid content of 40%. The positive electrode slurry is then coated on the positive electrode collector aluminum foil, dried at 60°C, and then rolled and die-cut to obtain the positive electrode sheet.
[0127] Preparation of negative electrode sheet: The negative electrode active material hard carbon, the second conductive agent conductive carbon black, the wetting agent sodium carboxymethyl cellulose, and the second binder styrene-butadiene rubber are mixed in a mass ratio of 95:2.5:1.0:1.5. During the mixing process, deionized water is used to prepare the mixture into a negative electrode slurry with a solid content of 40%. The negative electrode slurry is then coated on the negative electrode collector aluminum foil, dried at 80°C, and then rolled and die-cut to obtain a negative electrode sheet.
[0128] Preparation of electrolyte: Prepare one shot of electrolyte according to the following mass percentages: 12wt% sodium hexafluorophosphate, 10wt% propylene carbonate, 42wt% ethylene glycol dimethyl ether, 32wt% ethyl acetate, 1.5wt% vinylene carbonate, 0.5wt% fluoroethylene carbonate, 0.5wt% vinyl sulfate, 0.5wt% tri(trimethylsilyl) phosphate, 1.0wt% lithium difluorooxalatoborate to obtain one shot of electrolyte; prepare two shots of electrolyte according to the following mass percentages: 12wt% sodium hexafluorophosphate, 9wt% propylene carbonate, 42wt% ethylene glycol dimethyl ether, 25wt% ethyl acetate, 12wt% vinylene carbonate to obtain two shots of electrolyte.
[0129] Battery assembly: The positive and negative electrode sheets prepared above were stacked with a 12 μm thick ceramic-coated polypropylene (PP) separator using a stacking machine to obtain a 120 Ah coil core;
[0130] After welding the tabs to the core, the core is packaged with aluminum plastic film and baked at 85°C for 24 hours to obtain the core to be filled with liquid;
[0131] Inject one shot of electrolyte into the core to be filled with liquid to obtain one shot of battery cell. The injection coefficient of one shot of electrolyte is 3.0 / Ah.
[0132] After precharging and aging the one-shot battery cell, inject the second shot of electrolyte into the one shot to obtain the two-shot battery cell, and the injection coefficient of the second shot of electrolyte is 0.9g / Ah;
[0133] The two injected battery cells are formed in a 45°C incubator, and the steps are as follows: 1) Use a current of 0.1A to charge the battery cell for 2 hours, and the cut-off voltage is 3.0V; 2) The battery cell is aged in a 45°C incubator for 24 hours, and then taken out, vented, and repackaged; 3) Use a current of 1.33A to charge the battery cell at a constant current and constant voltage to 3.65V, and the cut-off current is 0.2A; 4) Use a current of 1.33A to discharge the battery cell at a constant current, and the cut-off voltage is 2.0V; 5) Continue to use a current of 1.33A to charge and discharge the battery cell in the range of 2.0V to 3.65V for 2 weeks to obtain a battery.
[0134] The preparation methods of Examples 2 to 3 are the same as those of Example 1, except that the mass proportion w0 of the first type of solvent in the solvent is adjusted.
[0135] The preparation methods of Examples 4 to 5 are the same as those of Example 1, except that the mass proportion w1 of the first type of additive and the mass proportion w2 of the solvent of the second additive in one injection of the electrolyte are adjusted.
[0136] The preparation methods of Examples 6 to 7 are the same as those of Example 1, except that the mass proportion of the third type of additive in the two injections of electrolyte is adjusted to w5.
[0137] The preparation methods of Examples 8 to 9 are the same as those of Example 1, except that the mass proportion of the positive electrode active material in the positive electrode material and the mass proportion of the negative electrode active material in the negative electrode material are adjusted.
[0138] The preparation method of Comparative Example 1 is the same as that of Example 1, except that the mass ratio of the first injection of electrolyte and the second injection of electrolyte is adjusted outside the range.
[0139] The preparation method of Comparative Example 2 is the same as that of Example 1, except that the mass proportion w0 of the first type of solvent in the solvent is adjusted to be outside the range.
[0140] The preparation method of comparative example 3 is the same as that of example 1, except that the mass proportion w1 of the first type additive and the mass proportion w2 of the solvent of the second additive in one injection of electrolyte are adjusted so that w1 / (w1+w2) is outside the range.
[0141] The preparation method of Comparative Example 4 is the same as that of Example 1, except that the mass proportion w5 of the third type of additive in the second injection of electrolyte is adjusted outside the range.
[0142] The preparation method of Comparative Example 5 is the same as that of Example 1, except that the mass proportion of the positive electrode active material in the positive electrode material and the mass proportion of the negative electrode active material in the negative electrode material are adjusted outside the range.
[0143] Test method:
[0144] (1) Test of electrolyte density: Use a pycnometer to test. Take a dried empty bottle and weigh it on a 1 / 10,000 balance. Then fill it with electrolyte (10 ml). Use a paper towel to absorb the electrolyte overflowing from the bottle wall and weigh it again. Divide the weight difference by the volume of the pycnometer and calculate the density according to the formula ρ = (m1-m2) / V. Where ρ represents the electrolyte density, m1 represents the weight of the pycnometer filled with electrolyte, m2 represents the weight of the dry empty pycnometer, and V represents the volume of the pycnometer.
[0145] Pole sheet surface density test: Use a 15mm diameter punch to press 10 coated and uncoated discs, weigh them separately and take the average value. The mass difference of the average value is the coating mass on a single disc. The total coating mass divided by the area of the disc gives the pole sheet surface density.
[0146] (3) Test of the compaction density of the pole piece: The above surface density is divided by the thickness of the pole piece coating to obtain the compaction density of the pole piece.
[0147] (4) Calculation method of filling coefficient: electrolyte filling mass / battery cell capacity.
[0148] (5) Calculation of battery cell energy density: Battery cell energy density = battery cell capacity * rated discharge voltage / total battery cell mass.
[0149] (6) 25°C / 45°C cycle test: The capacity retention rate after 500 cycles at 25°C and 45°C was tested respectively. At 25°C and 45°C, the battery cells of the above schemes were charged to 3.8V at 0.5C and then discharged to 1.5V at a constant current of 0.33C. The rated capacity and rated voltage of the battery cells were obtained, and the energy density of the battery cells was calculated.
[0150] (7) High temperature storage test: First, the battery was charged and discharged three times at 0.5C / 0.5C (3.8V~2.0V) at room temperature, and then the fully charged (DOD=100SOC%) battery was stored in a 60°C oven for 30 days. After being taken out, it was allowed to stand at room temperature for 4 hours, and then discharged at room temperature at 0.5C. Then, it was charged and discharged three times, and the last discharge capacity was recorded as the recoverable capacity.
[0151] Table 1 shows the parameter settings of Examples 1 to 9 and Comparative Examples 1 to 5.
[0152]
[0153]
[0154] Table 2 shows the test results of Examples 1 to 9 and Comparative Examples 1 to 5.
[0155]
[0156]
[0157] Results Analysis
[0158] From the test results of Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, due to the low mass ratio of the first injection of electrolyte in the total electrolyte, the battery cell is poorly wetted after the first injection, and lithium deposition occurs at the interface during pre-charging, resulting in a poor cycle life and capacity retention rate of the battery cell. Therefore, maintaining a reasonable mass ratio of the first injection and the second injection is very important for the process and cycle performance of the battery.
[0159] From the test results of Examples 1 to 3 and Comparative Example 2, it can be seen that in Comparative Example 2, since more carbonate solvents are used as solvents, and the proportion of propylene carbonate reaches 18%, the average density of the electrolyte is higher, the injection coefficient is also higher, the mass proportion of the electrolyte in the battery is also higher, and the energy density of the battery cell is only 108wh / kg; therefore, by using less cyclic carbonates and more linear solvents as solvents, the injection coefficient and injection amount of the electrolyte can be reduced, and the energy density of the battery cell can be increased to more than 110wh / kg.
[0160] From the test results of Example 1, Examples 4-5, and Comparative Example 3, it can be seen that in Comparative Example 3, since the mass percentage of the first type of additive in a single injection of electrolyte is relatively small (6.25%), the chemical stability of the film formation of the electrolyte decreases, and the high-temperature cycling performance and calendar life of the battery cell significantly decline; therefore, by controlling the mass percentage of the second type of additive and the first type of additive in a single injection of electrolyte to satisfy 10% < w1 / (w1 + w2) < 40%, the 25°C cycling life of the battery cell can meet more than 2000 cycles, the 45°C cycling life reaches more than 1500 cycles, and the capacity retention rate after 30 days of high-temperature storage is above 95%.
[0161] From the test results of Example 1, Examples 6-7, and Comparative Example 4, it can be seen that in Comparative Example 4, since the mass percentage of the third type of additive in the second injection of electrolyte is relatively low (4%), the cycling performance of the battery is poor and the storage capacity is small. Therefore, by controlling the mass percentage w5 of the third type of additive in the second injection of electrolyte to satisfy 5wt% < w5 < 15wt%, the cycling performance of the battery can be improved and the storage capacity of the battery can be increased.
[0162] From the test results of Example 1, Examples 8-9, and Comparative Example 5, it can be seen that in Comparative Example 5, the mass percentage of the positive active material in the positive electrode material is relatively low, and the mass percentage of the negative active material in the negative electrode material is relatively low, resulting in a relatively low mass percentage of the active material in the battery cell, and the energy density of the battery is only 108.5 wh / kg. Therefore, by making the mass percentage of the positive active material in the positive electrode material 95-96.5% and the mass percentage of the negative active material in the negative electrode material 95-96.5%, the energy density of the battery can be increased.
[0163] In summary, although the detailed introduction of the embodiments of the present application is as above, the above embodiments are not intended to limit the present application. Those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A battery, characterized in that: include: A positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises a first-injection electrolyte and a second-injection electrolyte, wherein the first-injection electrolyte and the second-injection electrolyte both comprise a first-type sodium salt and a solvent; the solvent comprises a first-type solvent and a second-type solvent, wherein the first-type solvent is selected from at least one of propylene carbonate and ethylene carbonate, and the second-type solvent is selected from at least one of linear carbonates, linear carboxylates and linear ethers, and the mass proportion of the first-type solvent is w0 based on the total mass of the solvent, satisfying the following: 8%≤w0≤15wt%.
2. The battery according to claim 1, characterized in that The electrolyte solution further includes a first type of additive and a second type of additive, wherein the first type of additive is selected from at least one of a second type of sodium salt and a second type of lithium salt, and the second type of additive is selected from esters; The first type of sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, and sodium tetraphenylborate; The linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate; The linear carboxylic acid ester is selected from at least one of ethyl acetate, methyl acetate and methyl propionate; The linear ether is selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; The second type of sodium salt is selected from at least one of sodium difluorophosphate, sodium difluorooxalatoborate, sodium tetrafluorooxalatophosphate, sodium trifluoromethanesulfonate, and sodium tetrafluoroborate; The lithium salt is selected from at least one of lithium difluorooxalatoborate and lithium tetrafluorooxalatophosphate; The ester is selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, and tris(trimethylsilyl)phosphate.
3. The battery according to claim 2, characterized in that Based on the total mass of the electrolyte, the mass proportion of the first type of additive is w1, and the mass proportion of the second type of additive is w2, which satisfies: 10% <w1 / (w1+w2)<40%; Based on the total mass of the electrolyte injection, the mass proportion of the first type of additive is w1, which satisfies: 0.5wt%≤w1≤1.0wt%; Based on the total mass of the one injection of electrolyte, the mass proportion of the second type of additive is w2, satisfying: 2.5wt%≤w2≤4.0wt%; Based on the total mass of the electrolyte injection, the mass proportion of the first type of sodium salt is w3, satisfying: 10wt%≤w3≤15wt%; Based on the total mass of the electrolyte solution, the mass proportion of the solvent is w4, satisfying: 80≤w4≤87wt%.
4. The battery according to claim 1, characterized in that The second electrolyte solution further includes a third type of additive, and the third type of additive is selected from vinylene carbonate; The first type of sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(trifluoromethylsulfonyl)imide, and sodium tetraphenylborate; The linear carbonate is selected from at least one of ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate; The linear carboxylic acid ester is selected from at least one of ethyl acetate, methyl acetate and methyl propionate; The linear ethers are selected from at least one of ethylene glycol dimethyl ether and diethylene glycol dimethyl ether.
5. The battery according to claim 4, characterized in that Based on the total mass of the two-injection electrolyte, the mass fraction of the third type of additive is w5, satisfying: 5wt% ≤ w5 ≤ 15%; Based on the total mass of the two-injection electrolyte, the mass fraction of the first type of sodium salt is w6, satisfying: 10wt% ≤ w6 ≤ 15wt%; Based on the total mass of the two-injection electrolyte, the mass fraction of the solvent is w7, satisfying: 70wt% ≤ w7 ≤ 85wt%.
6. The battery according to claim 1, characterized in that The mass ratio of the first-injection electrolyte to the second-injection electrolyte is 3 - 9:
1.
7. The battery according to claim 1, characterized in that The battery satisfies the following expressions: 110wh / kg < QU / m < 120wh / kg, and 15% < m1 / m < 20%; Wherein, Q represents the capacity of the battery, in units of wh; U represents the average discharge voltage of the battery when the discharge voltage is 1.5V to 3.8V, in units of V; m1 represents the mass of the electrolyte, in units of kg, and m represents the mass of the battery, in units of kg. The battery satisfies the following expressions: 110wh / kg < QU / m < 120wh / kg, and 15% < m1 / m < 20%.
8. The battery according to claim 1, characterized in that The average density of the electrolyte is ρ, satisfying: 1.10g / ml < ρ < 1.15g / ml; and / or The compaction density of the positive electrode is 2.1 to 2.3 g / cm 3 and / or, The surface density of the positive electrode is 20-22 mg cm -2 and / or, The compaction density of the negative electrode is 0.95 to 0.98 g / cm 3 and / or, The surface density of the negative electrode is 7.1-7.3 mg cm -2 ; and / or The positive electrode includes a positive electrode current collector and a positive electrode material located on at least one side of the positive electrode current collector. The positive electrode material includes a positive electrode active material, and the positive electrode active material is selected from at least one of sodium iron pyrophosphate phosphate and sodium iron phosphate. Based on the total mass of the positive electrode material, the mass fraction of the positive electrode active material is 95 - 96.5%; and / or The negative electrode includes a negative electrode current collector and a negative electrode material located on at least one side of the negative electrode current collector. The negative electrode material includes a negative electrode active material, and the negative electrode active material is selected from hard carbon. Based on the total mass of the negative electrode material, the mass fraction of the negative electrode active material is 95 - 96.5%.
9. A method for preparing a battery according to any one of claims 1 to 8, characterized in that: Including: Providing a positive electrode sheet, a negative electrode sheet, and a separator; Stacking the positive electrode sheet, the negative electrode sheet, and the separator to obtain a core; After encapsulating the core, obtaining a core to be filled with electrolyte; Injecting a first-injection electrolyte into the core to be filled with electrolyte to obtain a first-injection battery cell; After pre-charging and aging the first-injection battery cell, injecting a second-injection electrolyte into the first-injection battery cell to obtain a second-injection battery cell; After forming the second-injection battery cell, obtaining a battery.
10. The method for preparing a battery according to claim 9, characterized in that: The injection coefficient of the first-injection electrolyte is 2.8 - 3g / Ah; and / or The injection coefficient of the second-injection electrolyte is 0.6 - 1.0g / Ah.
Citation Information
Patent Citations
Electrolyte and mixed lithium-sodium ion battery comprising same
CN116742134A
Sodium ion battery and electric equipment
CN117059901A
Organic electrolyte and sodium ion battery comprising same
CN117393855A
Low-self-discharge sodium-ion battery electrolyte
CN117673468A
Low-temperature sodium-ion battery electrolyte and preparation method thereof, battery and power utilization device
CN117691181A